1H NMR‐based metabolomics reveal overlapping discriminatory metabolites and metabolic pathway disturbances between colorectal tumor tissues and fecal samples. Issue 6 (4th March 2019) - Lin, Yan; Ma, Changchun; Bezabeh, Tedros; Wang, Zhening; Liang, Jiahao; Huang, Yao; Zhao, Jiayun; Liu, Xinmu; Ye, Wei; Tang, Wan; Ouyang, Ting; Wu, Renhua
Abstract : Previous studies have compared fecal metabolites from healthy and colorectal cancer (CRC) patients to predict the pro‐CRC signatures. However, the systemic mechanistic link between feces and colonic tissues of CRC patients is still limited. The current study was a paralleled investigation of colonic tumor tissues and their normal adjacent tissues alongside patient‐matched feces by using 1 H nuclear magnetic resonance spectroscopy combined with pattern recognition to investigate how fecal metabolic phenotypes are linked to the changes in colorectal tumor profiles. A set of overlapping discriminatory metabolites across feces and tumor tissues of CRC were identified, including elevated levels of lactate, glutamate, alanine, succinate and reduced amounts of butyrate. These changes could indicate the networks for metabolic pathway perturbations in CRC potentially involved in the disruptions of glucose and glycolytic metabolism, TCA cycle, glutaminolysis, and short chain fatty acids metabolism. Furthermore, changes in fecal acetate were positively correlated with alterations of glucose and myo‐inositol in colorectal tumor tissues, implying enhanced energy production for rapid cell proliferation. Compared to other fecal metabolites, acetate demonstrated the highest diagnostic performance for diagnosing CRC, with an AUC of 0.843 in the training set, and a good predictive ability in the validation set. Overall, these associations provide evidence of distinct metabolic signatures and metabolic pathway disturbances between the colonic tissues and feces within the same individual, and changes of fecal metabolic signature could reflect the CRC tissue microenvironment, highlighting the significance of the distinct fecal metabolic profiles as potential novel and noninvasive relevant indicators for CRC detection. Abstract : What's new? While fecal testing for altered metabolite levels is a promising tool for colorectal cancer (CRC) screening, associations between specific metabolic disturbances and CRC remain unknown. Here, parallel analysis of CRC tissues and adjacent normal tissues and fecal samples obtained pre‐ and post‐operatively from the same patients reveals a link between fecal metabolic phenotype and metabolite changes in CRC. Discriminatory metabolites were detected across feces and CRC tissues. Among these metabolites was fecal acetate, which showed high diagnostic performance for CRC. The findings warrant further investigation of fecal metabolic signature as a non‐invasive means of early CRC detection.